2020
DOI: 10.1177/2150135120949462
|View full text |Cite
|
Sign up to set email alerts
|

Early Impact of the COVID-19 Pandemic on Congenital Heart Surgery Programs Across the World: Assessment by a Global Multi-Societal Consortium

Abstract: The coronavirus disease 2019 (COVID-19) pandemic currently gripping the globe is impacting the entire health care system with rapidly escalating morbidities and mortality. Although the infectious risk to the pediatric population appears low, the effects on children with congenital heart disease (CHD) remain poorly understood. The closure of congenital heart surgery programs worldwide to address the growing number of infected individuals could have an unintended impact on future health for COVID-19-negative pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…(16) Many protocols and guidelines have been proposed worldwide to establish a perioperative management issue for patients with congenital heart disease. (12,17,18) The similarity of the protocols is pre-operative screening for covid-19, separation of wards between COVID-free patients, and suspects avoiding contamination risks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) Many protocols and guidelines have been proposed worldwide to establish a perioperative management issue for patients with congenital heart disease. (12,17,18) The similarity of the protocols is pre-operative screening for covid-19, separation of wards between COVID-free patients, and suspects avoiding contamination risks.…”
Section: Resultsmentioning
confidence: 99%
“…(11) https://www.cambridge.org/core/terms. https://doi.org/10.1017/S1047951121001608 Pediatric and Congenital Heart Surgery programs worldwide were concerned due to their patients' unique particularities (12,13). A survey performed by the COVID-19 International Congenital Heart Surgery Taskforce identified a significant surgical volume impact in 52 countries.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those of other centers, as cited by Polo López et al, 9 who describe a 51 % reduction in major surgeries and a 54 % decrease in extracorporeal surgeries. Protopapas et al, 10 carried out a worldwide survey and observed that 51 % of the consulted departments of cardiovascular surgery decreased their throughput by more than 50 %.…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados son similares a los de otros centros como citan Polo López y col., 9 que describen una reducción de 51 % menos de cirugías mayores y 54 % menos de cirugías extracorpóreas. Protopapas y col., 10 realizaron una encuesta mundial y encontraron que 51 % de los servicios de cirugía cardiovascular consultados disminuyeron más de 50 % su producción. Los días de restricción en nuestro estudio se contaron como días hábiles desde el inicio de las medidas hasta el 31 de agosto de 2020, fecha en la que se retoma parte de la capacidad operativa.…”
Section: Discussionunclassified